Pendidikan Kesehatan Menggunakan Media Pop-Up Book terhadap Pengetahuan Siswa tentang Miopia Akibat Penggunaan Gadget - Siti Chasani; Mugi Nugraha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effectiveness of health education using Pop-Up Book media in increasing students' knowledge about myopia, which can occur due to excessive gadget use. This study used a Quasi-Experimental method with a One Group Pretest-Posttest design. Students' knowledge was measured before and after the Pop-Up Book health education intervention. The results showed a significant increase in knowledge after the intervention, with a p-value <0.05, confirming the effectiveness of Pop-Up Books as an educational medium. The conclusion is that Pop-Up Books are an effective, innovative learning medium for increasing students' understanding of eye health and the wise use of gadgets. Keywords: Gadget, Myopia, Eye Health, Health Education, Pop-Up Book